2022
DOI: 10.1038/s41467-022-28079-0
|View full text |Cite
|
Sign up to set email alerts
|

Modular assembly of the principal microtubule nucleator γ-TuRC

Abstract: The gamma-tubulin ring complex (γ-TuRC) is the principal microtubule nucleation template in vertebrates. Recent cryo-EM reconstructions visualized the intricate quaternary structure of the γ-TuRC, containing more than thirty subunits, raising fundamental questions about γ-TuRC assembly and the role of actin as an integral part of the complex. Here, we reveal the structural mechanism underlying modular γ-TuRC assembly and identify a functional role of actin in microtubule nucleation. During γ-TuRC assembly, a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 55 publications
(91 reference statements)
10
38
0
Order By: Relevance
“…1b). This fits with the fact that γ-TuRCs derived from cells where all GCP3 subunits bear a GFP tag would be expected to contain five GCP3-GFP subunits 1821, 24 .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…1b). This fits with the fact that γ-TuRCs derived from cells where all GCP3 subunits bear a GFP tag would be expected to contain five GCP3-GFP subunits 1821, 24 .…”
Section: Resultssupporting
confidence: 69%
“…This finding raises the possibility that γ-TuRCnucleated microtubules may not be fully attached to their template, and some protofilaments might have a flared conformation that would permit CAMSAP binding. Furthermore, since the microtubulenucleating activity of purified γ-TuRC turned out to be quite low 18,22 , a potential mechanism of stimulating nucleation would be to alter γ-TuRC conformation to make it more similar to the microtubule structure 6,7,23,24 . To explore these possibilities, we have set up in vitro reconstitution assays and confirmed that purified γ-TuRC has by itself a rather low activity that can be enhanced by nucleation-promoting factors, microtubule polymerase chTOG, and γ-TuRC associated protein CDK5RAP2 [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Cloning of the MultiBac TM (GENEVA Biotech) constructs, all with polH expression cassettes, was done as described previously 50 , 51 , tagging individual proteins inspired by 24 . Genes of the X. laevis augmin TII and TIII complexes (HAUS1 (XM_018267162.1), HAUS2 (NP_001085195.1), HAUS3 (XM_018226568.1), HAUS4 (NM_001096090.1), HAUS5 (XM_018226568.1), HAUS6 (NM_001097095.1), and HAUS7 (NP_001121229.1)) were purchased (Integrated DNA Technologies IDT, USA) optimised for insect cell expression.…”
Section: Methodsmentioning
confidence: 99%
“…The assembly of γ-TuRC is modular, starting with the formation of a stable subcomplex of six spokes, consisting of GCP2-3-4-5-4-6, which then expands with the addition of four preformed GCP2-3 units (γ-TuSC), MZT1, and actin (Würtz et al, 2022). DNAseI binds directly to actin with high affinity.…”
Section: Figurementioning
confidence: 99%
“…The in vitro nucleation activity of isolated endogenous γ-TuRC was markedly inhibited after treatment with DNAseI, and saturation of DNAseI with actin abolished this inhibition, suggesting a functional importance of actin in the complex (Liu et al, 2020). Actin has been shown not to be required for assembly of γ-TuRC, but to determine the geometry of the complex and ensure effective nucleation of microtubules (Würtz et al, 2022). On the outer surface of reconstituted γ- (Zupa et al, 2021).…”
Section: Figurementioning
confidence: 99%